Prevalence of tuberculosis among prisoners in sub-Saharan Africa: a systematic review and meta-analysis - Sisay Asgedom, Yordanos; Ambaw Kassie, Gizachew; Melaku Kebede, Tsegaye (Frontiers in Public Health, 2023)
Background Tuberculosis (TB) is a key community health problem in numerous settings, predominantly in sub-Saharan Africa (SSA). TB is the second most lethal infectious disease worldwide. Around 1.6 million people died from TB in 2021. TB prevention and control strategies are difficult to implement in prison, especially in sub-Saharan Africa, owing to overcrowding and poor ventilation. Thus, this systematic review and meta-analysis aimed to synthesize the estimated pooled prevalence of tuberculosis among prisoners in sub-Saharan Africa. Materials and methods Electronic biomedical databases such as Google Scholar, Web of Science, PubMed/Medline, EMBASE, and Science Direct were used to systematically explore candidate studies published until December 2022. Data extraction was performed using a Microsoft Excel spreadsheet. The estimated pooled prevalence of tuberculosis was determined using a fixed-effects model. Cochrane Q-test and I2 statistics were used to check heterogeneity statistically across different studies. Begg’s rank and Egger’s tests were performed to assess evidence of possible publication bias. Results A total of 40 articles involving 59,300 prisoners were included in this systematic review and meta-analysis. The pooled prevalence of tuberculosis was 4.02% (95% CI: 2.68–5.36). We found the highest prevalence using Gene X pert as a diagnostic method, which was 4.97 (95% CI: 2.22–7.73). There is no evidence of publication bias. Conclusion The outcome of this review revealed a high prevalence of tuberculosis among prisoners in sub-Saharan Africa. To reach the “End Tuberculosis strategy” by 2030, early identification of cases through screening on entry and periodical active case finding is important. Moreover, prevention and prompt treatment after diagnosis must be implemented to limit transmission to the general population. Systematic review registration https://www.crd.york.ac.uk/prospero/#searchadvanced, identifier (CRD42023428933).